The Impact of Digital Transformation on Operational Efficiency and Strategic Decision Making in Industrial Companies - Manohar, Mekala (My University, 2026)
The contemporary industrial organizations have made digital transformation a significant competitiveness and innovation driver. This thesis will research on how digital transformation affects the efficiency of operations and strategy formulation of industrial firms and explore the obstacles to effective digital transformation. The study is a quantitative study that relies on a structured questionnaire that will be sent to the employees of industrial companies. One hundred valid responses were taken and processed with the help of statistical methods and descriptive statistics, correlation analysis, regression analysis, and analysis of variance (ANOVA). The results show that the digital transformation has a strong positive effect on the operational efficiency and strategic decision-making. Those organizations that embrace the use of digital technologies, including automation systems, data analytics, and integrated digital platforms, record higher productivity, a more efficient workflow, and quality decisions. It is also indicated in the results that digital tools facilitate data-driven strategic planning and make the process of decision-making faster and more accurate. Nevertheless, the research points to a number of obstacles that adversely affect the success of digital transformation, such as the unwillingness to change organisations, the absence of digital skills, the lack of training, the financial factors and the challenges of integrating the new systems with the old ones. On the whole, the research finds that digital transformation could be used to improve organizational performance in industrial firms to a great degree, although the strategy of its implementation, training of employees, and effective leadership support are essential.
Keywords: digitalisation; industry; organisations (systems); strategic planning; industrial companies; organisational changes; digital technology; strategic leadership; digital competence; enterprises; fi=Aluetiede|en=Regional Studies|; Master’s Programme in Industrial Engineering and Management; Industrial Management